2022
DOI: 10.3390/machines10020122
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic System Modeling of a Hybrid Neural Network with Phase Space Reconstruction and a Stability Identification Strategy

Abstract: Focusing on the identification of dynamic system stability, a hybrid neural network model is proposed in this research for the rotating stall phenomenon in an axial compressor. Based on the data fusion of the amplitude of the spatial mode, the nonlinear property is well characterized in the feature extraction of the rotating stall. This method of data processing can effectively avoid the inaccurate recognition of single or multiple measuring sensors only depending on pressure. With the analysis on the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…When entering the rotating stall stage, the modal amplitude starts to fluctuate greatly. The same analysis is also confirmed in the literature [13], showing the repeatability of the reported results. It is concluded that the essential characteristic of the compressor system is captured by the increment in amplitude of modal energy in the gradual process of stall development.…”
Section: Feature Extraction Of Spatial Mode In Time-domainsupporting
confidence: 90%
See 1 more Smart Citation
“…When entering the rotating stall stage, the modal amplitude starts to fluctuate greatly. The same analysis is also confirmed in the literature [13], showing the repeatability of the reported results. It is concluded that the essential characteristic of the compressor system is captured by the increment in amplitude of modal energy in the gradual process of stall development.…”
Section: Feature Extraction Of Spatial Mode In Time-domainsupporting
confidence: 90%
“…The inception can be suggested by about 12-68 revolutions before the stall arrival. On this basis, a hybrid neural fusion network was proposed by Zhang to represent the properties of a compressor system by artificial intelligence learning [13]. By taking the identification strategy with sample entropy and a difference quotient criterion, an inception warning can be suggested in advance with a multi-step prediction of a neural network.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant geometric parameters of the compressor are presented in Table 1 for a brief synopsis. An introduction on the test rig is described in the references [ 15 ].…”
Section: Data Acquisition and Phase Space Processingmentioning
confidence: 99%
“…By the stall data training with Long Short Term Memory (LSTM), the regression model was adopted in the neural network of the compressor [ 14 ]. The rotating stall of the axial flow compressor was predicted based on the K-means-GD-RBF fusion model [ 15 ] reconstructed from the phase space of the chaotic sequence. The global sample entropy was employed to detect the stall precursor in advance according to the difference quotient discrimination strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation